Rural English Language Teacher Identities: Alternative Narratives of Professional Success - Ferney Cruz-Arcila (Ikala: Revista de Lenguaje y Cultura, 2020)
This paper problematizes the notion of professional success in English language teaching as constructed in language policy in Colombia. This is done by examining one of the most underexplored social diversities in the field: rural schools. Stemming from a narrative study on how rural English language teachers configure their professional identities vis-à-vis the situated circumstances of their work settings and external pressures, this analysis shows that teachers’ sense of professional success is negotiated in creative, complex, and multiple—although not always consistent—ways, which represent alternative constructions of good teaching to those promulgated in policy. It is argued, then, that a reconfiguration of the belief systems of what teachers should know and do is necessary